(untitled) (Experimental biology, 2015)
Lipid peroxidation (LPO) and alterations in cellular systems protecting against oxidative damage were determined in the liver of male albino rats, 4 weeks after intraperitoneal (i.p) injection of 0.5 ml/kg bw of crude oil and/or oral consumption of 150 mg V /L or 180 mg Ni /L. After subjecting the rats to crude oil or vanadium or nickel, LPO level and serum alanine-(ALT) and aspartate-(AST) transaminases activities were raised (p